Trading in Air Bangis in the 19th Century - Junaidi Junaidi; Ratna Ratna (Humaniora, 2019)
This study aims to explain trading activities at the Air Bangis harbor during the Dutch Colonial Government. Since the early 19th century, the Dutch Colonial Government had been more ambitious than before to utilize as much forest and agricultural products as possible in the hinterland of the West Coast of Sumatra. This intention was also supported by the improvement of the functions of harbor cities along the West Coast of Sumatra, including Air Bangis. The improvement per se had allowed a small-scale trade to be upgraded to export-oriented free harbors. The high level of trading activity in the Air Bangis harbor was made possible by its hinterland which is rich in export commodities. Among the types of the export commodities were gold, camphor, myrrh, rattan, dammar, coffee and pepper. The Air Bangis harbor had a role in lifting the spirits of the foreign nations, such as Aceh, VOC, English, and the Dutch Colonial Government, to build their influences in the harbor. The competition often caused friction which resulted in a conflict and power overtaking. The winners would take over the power from the losers, established their hegemony and monopolized the trade in the area of Air Bangis. The prosperity of the maritime activities in Air Bangis reached its peak in the first quarter of the 19th century, but it did not last long. In the last quarter of the 19th century, maritime activities in Air Bangis harbor started to decline. Nevertheless, sea voyage and trading activities in Air Bangis harbor had given a specific color to the maritime world in the West Sumatera Coast.